2023
DOI: 10.2147/ijn.s392782
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide/Gelatin Nanofibrous Scaffolds Loaded with N-Acetyl Cysteine for Promoting Wound Healing

Abstract: Purpose We aimed to develop an antioxidant dressing material with pro-angiogenic potential that could promote wound healing. Gelatin (Gel) was selected to improve the biocompatibility of the scaffolds, while graphene oxide (GO) was added to enhance their mechanical property. The loaded N-Acetyl cysteine (NAC) was performing the effect of scavenging reactive oxygen species (ROS) at the wound site. Materials and Methods The physicochemical and mechanical properties, NAC r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Stem cells can promote the production of transforming growth factor-β3 (TGF-β3), VEGF, and insulin growth factor (IGF) through paracrine, promoting cell migration and vascular regeneration ( Chen et al, 2021 ). Yu et al, 2023 reduced graphene oxide (GOG) by gelatin to increase its compressive strength for the delivery of N-acetylcysteine (NAC) to obtain NAC-GO-Gel. GO-Gel stents have good biocompatibility and promote neovascularization ( Shen et al, 2022 ).…”
Section: Gelatin-based Biomaterials Promote Wound Healingmentioning
confidence: 99%
“…Stem cells can promote the production of transforming growth factor-β3 (TGF-β3), VEGF, and insulin growth factor (IGF) through paracrine, promoting cell migration and vascular regeneration ( Chen et al, 2021 ). Yu et al, 2023 reduced graphene oxide (GOG) by gelatin to increase its compressive strength for the delivery of N-acetylcysteine (NAC) to obtain NAC-GO-Gel. GO-Gel stents have good biocompatibility and promote neovascularization ( Shen et al, 2022 ).…”
Section: Gelatin-based Biomaterials Promote Wound Healingmentioning
confidence: 99%
“…Gelatin (Gel) was chosen to improve scaffold biocompatibility, N ‐acetyl cysteine (NAC) was loaded into the scaffold to scavenge ROS at the wound site, while GO was incorporated to provide self‐healing and mechanical strength. Results demonstrated that the NAC‐GO‐Gel scaffold exhibited superior mechanical properties and sustained NAC release compared to Gel alone, leading to enhanced cell proliferation and migration 210 …”
Section: Recently Used Self‐healing Materials In Wound Therapymentioning
confidence: 99%
“…[29][30][31] On the other hand, electrospun nanofibers are constantly being used in new and innovative applications due to their ability to encapsulate active ingredients for specific purposes. [32][33][34] Additionally, it is easy to load multiple active ingredients into complex electrospun structures with the ability to tailor components, compositions, and spatial distributions within nanofibers. 35 As a result, this is a powerful method for achieving multiple functional benefits and achieving a designed synergistic effect.…”
Section: Introductionmentioning
confidence: 99%